The future of AFG : how family attachment influenced growth - Polano, Francesco, (SAGE Knowledge. Cases., 2013)
The case deals with a dilemma the Italian family firm AFG faced after making a significant investment to grow its business. AFG had been a successful commercial dealer of food packaging plastics, but under increased competition and squeezed margins, it bought an extrusion plant to become a manufacturer of plastic packaging for the food industry. AFG's owner, Mauro Polano, wanted a stronger market position. The plant was, however, defective, underperforming at two-thirds of the promised capacity and causing financial loss. As CEO, Mauro had to decide whether to (1) invest in a new plant to make up for the under-promised capacity of the current one, (2) stop production for two months, repair the plant, and fix all defects, or (3) sell the flawed plant and return to the market as a commercial intermediary. Because AFG was a family firm, both the first priority and end goal was to guarantee a good life for his family and ensure an even better future for his children, who would eventually take over the business.